Wirausaha Kreatif: Inovasi Tanpa Batas - Johnny Chandra; Hommy Dorthy Ellyany Sinaga; Elisabeth Nainggolan; Claudie Tiofanny (PT. Gudang Pustaka Cendekia, 2025)
Kegiatan pengabdian kepada masyarakat dengan tema